Water availability influences both wood anatomy and laticifer density in rubber tree saplings - Nery, Ícaro Renã Alves Moureira [UNESP]; Vergilio, Paula Cristina Benetton [UNESP]; Viégas, Lucas Bertacini [UNESP]; da Silva, Magali Ribeiro [UNESP]; Resende, Rafael Tassinari; Chagas, Matheus Peres; Pace, Marcelo Rodrigo [UNESP]; Marcati, Carmen Regina [UNESP] (Elsevier, 2023)
Given the predicted intensification of droughts and floods in the context of climate change, it is critical to understand the effect of water availability on secondary xylem and laticifers in rubber trees (Hevea brasiliensis (Willd. ex A.Juss.) Müll.Arg, Euphorbiaceae). Thus, we investigated the effects of different substrate water availability treatments on anatomical features of the secondary xylem, and the diameter, density, and proportion of laticifers in saplings of rubber trees. Lower substrate water availability resulted in shorter fibers and higher fiber fraction, lower gelatinous fiber fraction, higher vessel density, and lower laticifer density. Under lower water availability, changes in the secondary xylem favor safety in water transport. In the case of laticifers, which are present in the secondary phloem, their structural characteristics may represent a significant decrease in the latex production capacity, which in large forest plantations may reflect economic losses.
Keywords: Euphorbiaceae; Fibers; Hevea brasiliensis; Secretory structures; Vessels